PREVALENCE OF SILENT MYOCARDIAL ISCHEMIA IN MIDDLE-AGED PATIENTS WITH TYPE 2 DIABETES MELLITUS - Kishko, Oleksandr; Kishko, Nelli; Derňarová, Ľubica (Проблеми клінічної педіатрії, 2019)
Myocardial ischemia is often asymptomatic in patients with type 2 diabetes mellitus (T2DM) and coronary artery disease (CAD) is frequently in an advanced stage when it becomes clinically manifested. Silent myocardial ischemia (SMI) is defined as objective evidence of myocardial ischemia in the absence of typical chest discomfort or other anginal equivalents. Aim To test for LV function to assess the risk of silent myocardial ischemia(SMI) and to determine the relationship between abnormal perfusion tomography and the incidence of cardiac events in asymptomatic patients with middle-aged T2DM and to further evaluate the effectiveness of “aggressive” prevention strategies. Metods. We retrospectively analysed medical records of 192 (110 male pts; 57.3%) chronologically consecutive asymptomatic middle-aged (≤60 years) patients with T2DM, who had undergone MPI subsequently followed by coronary angiography in case perfusion abnormalities were found. MPI was performed from 2010 to 2014 at a single outpatient care centre with nuclear medicine unit, according to the EANM procedural guidelines for stressrest ECG gated SPECT one-day protocol using 99mTc-tetrofosmin (Verberne et al., 2015). Results. Data confirm a relatively high prevalence of silent myocardial ischemia (SMI) in elderly patients with type 2 diabetes mellitus (T2DM), while no data are available regarding middle-aged subjects (≤60 years). Medical records of 192 patients with T2DM aged ≤60 years (110 male patients; 57.3%), who had undergone myocardial perfusion imaging (MPI) between 2010 and 2014 followed by coronary angiography in case of abnormal result, were retrospectively analysed.MPI was positive in 35 patients (18.2%); of those 31 (88.6%) had angiographically confirmed coronary stenosis. The positive predictive value of the MPI for predicting angiographic coronary stenosis in this age subgroup was 88.9%. Univariate analysis revealed post-stress LVEF drop ≥5% (p<0.03) and NT-proBNP levels detected in stress (p<0.05) to be associated with greater risk of ischemia in working-age T2DM patients. In multivariate analysis, LVEF drop ≥5% (p< 0.03) remained an independent predictor of SMI. Prevalence of SMI in diabetic middle-aged patients was similar to that observed in studies of subjects over 65 years-old. Post-stress LVEF drop ≥5% and NT-proBNP levels can contribute to more precise identification of SMI. Our data suggest that “aggressive” management strategy should be implemented to reduce the risk of cardiac events in T2DM patients of middle age. Conclusion. The presented data address only the prevalence, severity, and possible predictors of SMI at the time of enrolment into the study and suggest that advanced intervention procedures including “aggressive” drug management should be implemented to reduce the risk of cardiac events in forthcoming future. Follow-up evaluation should allow to define the relationship between abnormal perfusion imaging and the prevalence of cardiac events in asymptomatic middle-aged T2DM patients and to evaluate the effectiveness of “aggressive” preventive strategies.